2017
DOI: 10.3847/1538-4357/835/2/148
|View full text |Cite
|
Sign up to set email alerts
|

Internal Gravity Waves in the Magnetized Solar Atmosphere. I. Magnetic Field Effects

Abstract: Observations of the solar atmosphere show that internal gravity waves are generated by overshooting convection, but are suppressed at locations of magnetic flux, which is thought to be the result of mode conversion into magneto-acoustic waves. Here, we present a study of the acoustic-gravity wave spectrum emerging from a realistic, self-consistent simulation of solar (magneto-)convection. A magnetic field free, hydrodynamic simulation and a magneto-hydrodynamic (MHD) simulation with an initial, vertical, homog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 54 publications
4
36
0
Order By: Relevance
“…Low-frequency ultraviolet (UV) brightness fluctuations observed in the internetwork region of the low solar chromosphere are believed to be caused by IGWs dissipating in the higher layers [2]. However, the strong effects of magnetic field orientation (attack angle) on the propagation of IGW have been demonstrated by Newington & Cally [3,4] and realistic numerical simulations have shown that the magnetic field present in the solar atmosphere influence the propagation of these waves and likely hinder them from propagating into the upper atmosphere [5][6][7]. At this point, it is still unclear what role the magnetic field plays in the propagation of IGWs into higher layers and how this fits with the brightness fluctuations seen in chromosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency ultraviolet (UV) brightness fluctuations observed in the internetwork region of the low solar chromosphere are believed to be caused by IGWs dissipating in the higher layers [2]. However, the strong effects of magnetic field orientation (attack angle) on the propagation of IGW have been demonstrated by Newington & Cally [3,4] and realistic numerical simulations have shown that the magnetic field present in the solar atmosphere influence the propagation of these waves and likely hinder them from propagating into the upper atmosphere [5][6][7]. At this point, it is still unclear what role the magnetic field plays in the propagation of IGWs into higher layers and how this fits with the brightness fluctuations seen in chromosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In relatively weak magnetic regions of the lower solar atmosphere, gravity waves with frequencies shorter than 2 mHz (periods 500 s) have been identified in both observations and simulations [30][31][32][33]. Such waves have been found to have larger energy flux, by approximately one order of magnitude, compared to co-spatial acoustic waves [34], and thus can potentially contribute towards heating of the chromosphere and beyond.…”
Section: (C) Gravity Wavesmentioning
confidence: 91%
“…IGWs have also been proposed as an agent for the mechanical heating of stellar atmospheres and coronae [10]. More recent studies [11][12][13] show the diagnostic potential of the IGWs for magnetic field in the solar atmosphere at different heights above the solar surface.…”
Section: Introductionmentioning
confidence: 99%